2018
DOI: 10.1098/rsbl.2018.0443
|View full text |Cite
|
Sign up to set email alerts
|

The effects of male harm vary with female quality and environmental complexity in Drosophila melanogaster

Abstract: Mate competition provides the opportunity for sexual selection which often acts strongly on males, but also the opportunity for sexual conflict that can alter natural selection on females. Recent attention has focused on the potential of sexual conflict to weaken selection on females if male sexual attention, and hence harm, is disproportionately directed towards high- over low-quality females, thereby reducing the fitness difference between these females. However, sexual conflict could instead strengthen sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…The fact that male preference for young females may have been more marked in the FB social context could have led males to be more harmful to these females, which in turn may have counterbalanced any benefits from male mate choice. As a matter of fact, Long, Pischedda, Stewart, and Rice () showed that male harm is preferentially directed toward intrinsically higher‐fitness females and that, as a result, any fitness advantage that could be experienced by high condition females (young females in our design) might be compensated by the costs of being attractive in a FB social context (at least in simple environments such as the one used in this experiment; see Yun, Chen, Singh, Agrawal, & Rundle, ; MacPherson, Yun, Barrera, Agrawal, & Rundle, ). Similarly, relatively high mating costs in a MB social context might also contribute to explain why we did not observe a sex ratio × female age interaction.…”
Section: Discussionmentioning
confidence: 93%
“…The fact that male preference for young females may have been more marked in the FB social context could have led males to be more harmful to these females, which in turn may have counterbalanced any benefits from male mate choice. As a matter of fact, Long, Pischedda, Stewart, and Rice () showed that male harm is preferentially directed toward intrinsically higher‐fitness females and that, as a result, any fitness advantage that could be experienced by high condition females (young females in our design) might be compensated by the costs of being attractive in a FB social context (at least in simple environments such as the one used in this experiment; see Yun, Chen, Singh, Agrawal, & Rundle, ; MacPherson, Yun, Barrera, Agrawal, & Rundle, ). Similarly, relatively high mating costs in a MB social context might also contribute to explain why we did not observe a sex ratio × female age interaction.…”
Section: Discussionmentioning
confidence: 93%
“…(82, 83)). Moreover, variation in overall phenotypic and genetic condition (84, 85), as well as the amount of male harm inflicted on females (86), could have masked a putative trade-off. Alternatively, trade-offs with PO investment could materialize for other life-history traits (9,30,87), and/or other components of immunity (22, 55) (see: Figure 1a and further below).…”
Section: Resultsmentioning
confidence: 99%
“…; MacPherson et al. ; Supporting Information). Compared to vials, male–female interactions in cages are less frequent and are less biased toward high‐quality females.…”
Section: Discussionmentioning
confidence: 99%
“…Given the observed differences between MC simple and MC complex , our results are inconsistent with a simple "monogamy versus polygamy" perspective. The MC simple and MC complex treatments both allow for mate competition and polygamy, but we have previously shown these mating environments differ with respect to the importance of sexual conflict (Yun et al 2017;MacPherson et al 2018;Supporting Information). Compared to vials, male-female interactions in cages are less frequent and are less biased toward high-quality females.…”
Section: Local Adaptation In Reproductive Fitnessmentioning
confidence: 98%